Fast Food Consumption Patterns Nutritional Status and Anemia Among Female - Herta Masthalina; Melly Purba; Lampita Pangaribuan (Postgraduate, University of Mataram, 2024)
This study aims to analyze the patterns of fastfood consumption, nutritional status, and prevalence of anemia among female students in the Nutrition Department of Poltekkes Medan. An observational method with a cross-sectional design was used on 73 female students. Data on the frequency of fastFood consumption was collected using a semi-quantitative FFQ, nutritional status was assessed based on BMI, and hemoglobin levels were measured using the Cyanmethemoglobin method. The results showed that 45.20% of respondents frequently consumed fast food, with an obesity prevalence of 35.70% and anemia prevalence of 35.60%. There was a significant relationship between fast food consumption and nutritional status (p=0.042), but not with anemia status (p=0.540). In conclusion high fastfood consumption correlates with obesity and anemia. Efforts are needed to increase the availability of healthy food on campus and further research on the long-term impact of ast Food consumption on student health.